HELEN, a Modular Framework for Representing and Implementing Clinical Practice Guidelines - Skonetzki, S.; Gausepohl, H.-J.; Haak, M. van der; Knaebel, S.; Linderkamp, O.; Wetter, T. (Methods of Information in Medicine, 2004)
Objectives: In order to implement clinical practice guidelines for the Department of Neonatology of the Heidelberg University Medical Center we developed a modular framework consisting of tools for authoring, browsing and executing encoded clinical practice guidelines (CPGs).Methods: Based upon a comprehensive analysis of literature, we set up requirements for guideline representation systems. Additionally, we analyzed further aspects such as the critical appraisal and known bridges and barriers for implementing CPGs. Thereafter we went through an evolutionary spiral model to develop a comprehensive ontology. Within this model each cycle focuses on a certain topic of management and implementation of CPGs.Results: In order to bring the resulting ontology into practice we developed a framework consisting of a tool for authoring, a server for web-based browsing, and an engine for the execution of certain elements of CPGs. Based upon this framework we encoded and implemented several CPGs in varying medical domains.Conclusions: This paper shall present a practical framework for both authors and implementers of CPGs. We have shown the fruitful combination of different knowledge representations such as narrative text and algorithm for implementing CPGs. Finally, we introduced a possible approach for the explicit adaptation of CPGs in order to provide institution-specific recommendations and to support sharing with other medical institutions.
Keywords: Clinical practice guidelines; representation; acquisition; implementation; local adaptation; execution; decision support